Perceptions of intensive care unit nurses of therapeutic futility: A scoping review - Vieira, João Vítor (2020)
Introduction: Intensive care units are contexts in which, due to the remarkable existence of particularly technological resources, interventions are promoted to extend the life of people who experience highly complex health situations. This ability can lead to a culture of death denial where the possibility of implementing futile care and treatment cannot be excluded. Objective: To describe nurses’ perceptions of adult intensive care units regarding the therapeutic futility of interventions implemented to persons in critical health conditions. Method: Review of the literature following the Scoping Review protocol of the Joanna Briggs Institute. The Population, Concept, and Context mnemonic was used to elaborate the research question and the research was performed using the EBSCOHost search engine in the CINAHL Complete databases, MEDLINE Complete, Cochrane Central Register of Controlled Trials, and Cochrane Database of Systematic Reviews to identify studies published between 1990 and 2019. Seven studies were selected. Results: Nurses consider that therapeutic futility, a current problem in adult intensive care units, may have a negative impact on persons in critical health conditions and that contributes directly to resource expenditure and moral conflicts and consequently leads to emotional exhaustion. Conclusion: Due to the complexity of this concept, knowing and understanding people’s and families’ perceptions is crucial to the decision-making process, for which reason nurses can play a key role in managing these situations.